OCSiAl highlights the efficacy of its graphene nanotubes as antistatic agents in PU. Issue 12 (December 2018) - Unknown
Abstract : Carbon nanomaterials specialist OCSiAl has provided new data demonstrating the ability of its graphene nanotubes to impart permanent and homogeneous antistatic properties to poly-urethane (PU) materials. Its Tuball™ products are not only able to overcome the previous difficulties with nanotube dispersion in PU systems, but they are also effective replacements for the ammonium salts and carbon black antistatic agents conventionally used in PU applications, the company claims. OCSiAl's recently developed Tuball Matrix 202 nanotube-based concentrate is already establishing a foothold in PU applications such as antistatic shoes and printing rollers, the firm reports.